Analisis Pengaruh Transaksi Asing dan Domestik Terhadap Return Saham pada Perusahaan Sektor Jasa Yang Terdaftar di Bursa Efek Indonesia - Heriyanto, Randy; Oliyan, Fitra (Akuntansi dan Manajemen, 2020)
The growth of the service sector is the fastest development in 2017 reaching more than 40%. This will generate great interest in both domestic and foreign investors. This study aims to examine the effect of foreign transactions on domestic transactions on stock returns in service sector companies in 2016-2018. The data used in this study are secondary data obtained from daily stock price reports and daily foreign (buy) and domestic buy (sell) data. The technical analysis used is descriptive analysis and Pearson correlation analysis using IBM SPSS Statistics 2.0. Based on testing conducted will be known later whether there is a relationship between foreign transactions on stock returns